Effect of physical endurance on fighting and the level of sports performance in junior judokas - Lech, G.; Tyka, A.; Palka, T.; Krawczyk, R. (Archives of Budo, 2010)
This study attempted to produce answer to the question: Is physical endurance in judo contestant at junior age related to the adopted fighting strategy and the level of sports performance? Material and methods. The study covered 10 judo contestants from three clubs in Poland. First stage encompassed registration of their competitive activity level. On the basis of this record, contestant`s fighting activity, efficiency and level of performance was assessed. Another stage of the investigations focused of evaluation of their aerobic and anaerobic endurance on the basis of testing methods used in the Institute for Human Physiology in the University School of Physical Education in Krakow. The strength of the relationship was concluded based on the value of Spearman`s rank correlation coefficient. Results. As was observed on the basis of statistical analysis, level of anaerobic endurance shows strong relationship with the method of fighting observed among young judokas. Time to reach maximal power seems to be of particular importance. Its value correlated with efficiency of contestants` actions taken during second phase of fight and with the level of sports achievement. Conclusions. The results of the present study should be taken into consideration by judo club coaches during planning and implementation of training schedules among young contestants.